(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2022)
The Conference on the Future of Europe, inaugurated in occasion with the Day of the European Union (May 9th, 2021), remarks the new deal of European institutions and opens to a future of participative democracy, in which the impetus of initiative would be in the hands of European peoples, without any discrimination and any difference. The contribution aims to describe the future perspectives of the EU: From a common platform of participation to the construction of a “positive” model of democracy in order to renew the institutions of the Union.